PP50 Body Mass Index, Waist Circumference and Incident Coronary Heart Disease in the Million Women Study. (10th September 2013) - Canoy, D; Cairns, B J; Balkwill, A; Wright, F L; Reeves, G; Green, J; Beral, V
Abstract : Background: Body mass index (BMI) and waist circumference are measures of total and abdominal adiposity, respectively, and both relate to coronary heart disease (CHD) risk. However, these measures are highly correlated, and require large-scale studies to reliably examine their separate associations with incident CHD. We examined the prospective relation of BMI and waist circumference with incident CHD in a large UK population-based cohort. Methods: 0.5 million women (mean age = 60 years) without vascular disease or cancer completed a health and lifestyle questionnaire (1999 to 2005), and were followed prospectively for 5 years on average. Adjusted relative risks and cumulative incidence (first coronary hospitalisation or death) from age 55 to 74 years were calculated using Cox regression. Plasma apolipoproteins were assayed in 6, 295 randomly selected participants. Results: Over 10, 000 women had a first coronary event during follow-up. The risk for incident CHD increased with both increasing BMI and waist circumference. When BMI and waist circumference were cross-classified by one another, the risk for incident CHD increased with increasing BMI within each waist circumference category (< 70, 70–79.9, ≥ 79 cm) (P for trend < 0.05); similarly, the risk increased with increasing waist circumference within each BMI category (<25, 25–29.9, ≥30 kg/m 2 ) (P for trend < 0.05). The cumulative CHD incidence was lowest in women with BMI < 25 kg/m 2 and waist circumference < 70 cm, with 7% developing CHD between ages 55 and 74 years, and highest in women with BMI ≥ 30 kg/m 2 and waist circumference ≥ 80 cm, with 12% developing CHD. Similar associations were observed for apolipo protein B to A1 ratio which increased with increasing BMI and waist circumference particularly in non-obese women (P for trend <0.05). Conclusion: In this large cohort of UK women, BMI and waist circumference are separately and independently associated with incident coronary disease. An atherogenic pattern of apolipoprotein profile may partly mediate these associations.